Long-circulation high-magnification negative electrode material as well as preparation method and application thereof

By combining silicon powder, tin powder with graphene and carbon coating, combining tungsten oxide and phosphate protective layer, using lithium carbide and metal-organic framework technology, the problems of structural collapse and volume change in traditional negative electrode materials during high-ratio charging and discharge are solved, and efficient electrochemical performance and long-cycle stability are achieved.

CN120221630AActive Publication Date: 2025-06-27JIANGXI SHENGXIN ENERGY TECH CO LTD

Patent Information

Application Number
CN202510385681.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-29
Publication Date
2025-06-27
Estimated Expiration
2045-03-29

AI Technical Summary

Technical Problem

The structure of traditional graphite negative electrode materials collapsed during high-ratio charging and discharging, resulting in a decline in electrochemical performance. The volume of high-capacity materials such as silicon and tin changes greatly during lithium ion embedding and deintercalation, affecting the cycle life of the battery.

Method used

By compounding silicon powder, tin powder with graphene and carbon coating, a three-dimensional conductive network is constructed, combining tungsten oxide to form a protective layer, metaphosphoric acid decomposes to form an inorganic phosphate protective film, lithium carbide reacts with vinylidene fluoride to form a lithium fluorocarbon additive, optimizes the lithium ion transmission path, and prepares a metal-organic framework by hydrothermal reaction of ammonium metavanadate and terephthalic acid.

Benefits of technology

It significantly improves the long cycle stability and high rate performance of the negative electrode material, improves the conductivity, cycle stability and rate performance, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120221630A_ABST
    Figure CN120221630A_ABST
Patent Text Reader

Abstract

The invention provides a long-circulation high-rate negative electrode material as well as a preparation method and application thereof, and belongs to the technical field of negative electrode materials. Silicon powder, tin powder and graphene are compounded and subjected to carbon coating, a three-dimensional conductive network is constructed, volume expansion is relieved, and conductivity, cycling stability and rate capability are improved; tungsten oxide serves as an interface stabilizer to form a protective layer, side reaction is inhibited, interface impedance is reduced, and a conductive network is enhanced; metaphosphoric acid is decomposed to generate an inorganic phosphate protective film, and nitrogen-doped carbon generated by urea decomposition is combined, so that the interface stability and conductivity are remarkably improved, and the cycle life is remarkably prolonged; lithium carbide reacts with vinylidene fluoride to generate a lithium fluorocarbon additive, and lithium ions are released in stages to reduce the first lithium loss and stabilize an interface; a vanadium-based metal-organic framework prepared from ammonium metavanadate and terephthalic acid is combined with pre-embedded lithium and graphitized carbon coating, so that a lithium ion transmission path is optimized, and the performance of the lithium ion battery is improved. The synergistic modification measures improve the long cycle stability and high rate performance of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anode materials, and relates to a long-cycle and high-rate anode material, a preparation method thereof, and an application thereof. Background Art

[0002] In the research and development of lithium-ion batteries, the selection and optimization of anode materials are particularly important because the anode materials not only directly affect the energy density, cycle stability, and rate performance of the batteries, but also largely determine the safety and economy of the batteries. The performance of the anode materials is not only related to the use effect of the batteries, but also involves their reliability and cost-effectiveness in practical applications. Therefore, the development of high-performance anode materials is one of the key factors for improving the overall performance of lithium-ion batteries.

[0003] Traditional graphite anode materials have always been the mainstream choice for lithium-ion batteries due to their good electrical conductivity and chemical stability. However, although graphite has a relatively low cost and a mature production process, its theoretical specific capacity is low, which is very insufficient under the background of the demand for modern high-energy-density batteries. In addition, during high-rate charge and discharge processes, the graphite anode often exhibits a phenomenon of structural collapse, resulting in a sharp decline in its electrochemical performance, which limits its wide application in high-performance batteries.

[0004] To solve the deficiencies of graphite anode materials, researchers have actively explored high-capacity anode materials such as silicon and tin. These materials have significantly higher theoretical specific capacities. However, silicon and tin will generate significant volume changes during the process of lithium-ion insertion and extraction, resulting in expansion and contraction of the electrode materials during charge and discharge. This volume change not only causes pulverization and structural damage of the electrodes, but also affects the cycle life of the batteries, leading to a significant decrease in conductivity during high-rate charge and discharge, thereby limiting the output power and charge and discharge speed of the batteries. Summary of the Invention

[0005] In view of the above problems, the object of the present invention is to provide a long-cycle and high-rate anode material, its preparation method and application. In this study, silicon powder, tin powder and graphene are compounded and carbon-coated to construct a three-dimensional conductive network, relieve volume expansion and improve conductivity, cycle stability and rate performance; tungsten oxide is used as an interface stabilizer to form a protective layer, inhibit side reactions, reduce interface impedance and enhance the conductive network; metaphosphoric acid decomposes to generate an inorganic phosphate protective film, combined with nitrogen-doped carbon generated by the decomposition of urea, significantly improving interface stability, conductivity and cycle life; lithium carbide reacts with polyvinylidene fluoride to generate a lithium fluorocarbon additive, which reduces the first lithium loss and stabilizes the interface by releasing lithium ions in stages; ammonium metavanadate and terephthalic acid are used to prepare a vanadium-based metal-organic framework combined with pre-embedded lithium and graphitized carbon coating to optimize the lithium ion transmission path, improve the first Coulomb efficiency, rate performance and structural stability. These synergistic modification measures significantly improve the long-cycle stability and high-rate performance of the anode material.

[0006] To achieve this purpose, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a preparation method of a long-cycle and high-rate anode material, and the preparation method of the long-cycle and high-rate anode material includes:

[0008] S1: Mix silicon powder, tin powder and graphene and ball-mill to obtain a composite powder; react it with polyacrylonitrile in N-methylpyrrolidone, dry and then heat-treat to obtain carbon-coated composite particles; impregnate and react it with an ethanol solution of tungsten hexachloride and calcine to obtain first-modified carbon-coated composite particles;

[0009] S2: Mix the first-modified carbon-coated composite particles with metaphosphoric acid and urea in absolute ethanol, dry and then heat-treat to obtain modified composite particles;

[0010] S3: React lithium carbide with polyvinylidene fluoride in tetrahydrofuran, dry and then heat-treat to obtain a lithium fluorocarbon additive;

[0011] S4: Hydrothermally react ammonium metavanadate and terephthalic acid and then heat-treat to obtain a metal-organic framework; react it with lithium carbide in tetrahydrofuran and heat-treat to obtain a pre-embedded lithium composite powder, and react it with polyacrylonitrile to obtain a surface-coated metal organic polymer;

[0012] S5: Pre-disperse the surface-coated metal organic polymer with carboxymethyl cellulose, add the modified composite particles, lithium fluorocarbon additive and conductive carbon black to prepare a long-cycle and high-rate anode material.

[0013] Specifically, S1: Mix silicon powder, tin powder and graphene and then ball-mill them to obtain a composite powder. Add it and polyacrylonitrile into N-methylpyrrolidone and stir to coat. After drying, heat-treat it in an inert atmosphere to obtain carbon-coated composite particles; Immerse them in an ethanol solution of tungsten hexachloride for impregnation reaction and calcine to obtain the first modified carbon-coated composite particles;

[0014] S2: Mix the first modified carbon-coated composite particles with metaphosphoric acid and urea, and then uniformly disperse them in absolute ethanol. After reaction and drying, heat-treat them in an inert atmosphere to obtain modified composite particles;

[0015] S3: Disperse lithium carbide and polyvinylidene fluoride in tetrahydrofuran, stir and react, then dry, and subsequently heat-treat it in an inert atmosphere to obtain a lithium fluorocarbon additive;

[0016] S4: Add ammonium metavanadate and terephthalic acid into a mixed solvent, carry out a hydrothermal reaction, then filter, wash and dry to obtain a precursor substrate. Heat-treat it in an inert atmosphere to obtain a metal-organic framework; Disperse it and lithium carbide in tetrahydrofuran, stir and react, then dry to obtain a pretreated powder, and heat-treat it to obtain a pre-lithiated composite powder; Disperse the pre-lithiated composite powder in an N-methylpyrrolidone solution of polyacrylonitrile in an inert atmosphere to obtain a reaction solution, stir and react, and then rotary evaporate to obtain a surface-coated metal-organic polymer;

[0017] S5: Pre-disperse the surface-coated metal-organic polymer and carboxymethyl cellulose in deionized water to obtain a pretreated base liquid, then add the modified composite particles and the lithium fluorocarbon additive, disperse evenly, add conductive carbon black, and defoam to obtain a long-cycle high-rate anode material.

[0018] As a preferred technical solution of the present invention, in step S1, the mass ratio of the silicon powder to the graphene is 3-4:1, for example, it can be 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1 or 4.0:1, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0019] In some alternative embodiments, the mass ratio of the tin powder to the graphene is 2-3:1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0020] In some alternative embodiments, the mass ratio of the composite powder to polyacrylonitrile is 1:3 - 5. For example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8, or 1:5.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0021] In some alternative embodiments, the solid-liquid mass ratio of the composite powder and polyacrylonitrile to N-methylpyrrolidone is 1:3 - 5. For example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8, or 1:5.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0022] In some alternative embodiments, the temperature of the heat treatment is 500 - 600 °C. For example, it can be 500 °C, 510 °C, 520 °C, 530 °C, 540 °C, 550 °C, 560 °C, 570 °C, 580 °C, 590 °C, or 600 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0023] In some alternative embodiments, the time of the heat treatment is 2 - 4 h. For example, it can be 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, or 4.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0024] In some alternative embodiments, the concentration of the ethanol solution of tungsten hexachloride is 0.05 - 0.1 M. For example, it can be 0.050 M, 0.055 M, 0.060 M, 0.065 M, 0.070 M, 0.075 M, 0.080 M, 0.085 M, 0.090 M, 0.095 M, or 0.100 M. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0025] In some alternative embodiments, the mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:8 - 12. For example, it can be 100:8.0, 100:8.4, 100:8.8, 100:9.2, 100:9.6, 100:10.0, 100:10.4, 100:10.8, 100:11.2, 100:11.6, or 100:12.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0026] In some alternative embodiments, the calcination temperature is 500 - 550 °C, for example, it can be 500 °C, 505 °C, 510 °C, 515 °C, 520 °C, 525 °C, 530 °C, 535 °C, 540 °C, 545 °C or 550 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0027] In some alternative embodiments, the calcination time is 2 - 3 h, for example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0028] As a preferred technical solution of the present invention, in step S2, the mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:8 - 10, for example, it can be 100:8.0, 100:8.2, 100:8.4, 100:8.6, 100:8.8, 100:9.0, 100:9.2, 100:9.4, 100:9.6, 100:9.8 or 100:10.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0029] In some alternative embodiments, the mass ratio of the first modified carbon-coated composite particles to urea is 100:8 - 10, for example, it can be 100:8.0, 100:8.2, 100:8.4, 100:8.6, 100:8.8, 100:9.0, 100:9.2, 100:9.4, 100:9.6, 100:9.8 or 100:10.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0030] In some alternative embodiments, the solid-liquid mass ratio of the mixture of the first modified carbon-coated composite particles, metaphosphoric acid and urea to absolute ethanol is 1:5 - 6, for example, it can be 1:5.0, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9 or 1:6.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0031] In some alternative embodiments, the heat treatment temperature is 400 - 450 °C, for example, it can be 400 °C, 405 °C, 410 °C, 415 °C, 420 °C, 425 °C, 430 °C, 435 °C, 440 °C, 445 °C or 450 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0032] In some alternative embodiments, the time of the heat treatment is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0033] As a preferred technical solution of the present invention, in step S3, the mass ratio of lithium carbide to polyvinylidene fluoride is 1:1 - 2. For example, it can be 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.0. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0034] In some alternative embodiments, the solid - liquid mass ratio of lithium carbide and polyvinylidene fluoride to tetrahydrofuran is 1:9 - 10. For example, it can be 1:9.0, 1:9.1, 1:9.2, 1:9.3, 1:9.4, 1:9.5, 1:9.6, 1:9.7, 1:9.8, 1:9.9 or 1:10.0. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0035] In some alternative embodiments, the time of the stirring reaction is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0036] In some alternative embodiments, the first temperature of the heat treatment is 250 - 280 °C. For example, it can be 250 °C, 253 °C, 256 °C, 259 °C, 262 °C, 265 °C, 268 °C, 271 °C, 274 °C, 277 °C or 280 °C. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0037] In some alternative embodiments, the first time of the heat treatment is 1 - 2 h. For example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h. However, it is not limited to the listed values, and other unlisted values within this value range are equally applicable.

[0038] In some alternative embodiments, the second temperature of the heat treatment is 400 - 450 °C. For example, it can be 400 °C, 405 °C, 410 °C, 415 °C, 420 °C, 425 °C, 430 °C, 435 °C, 440 °C, 445 °C or 450 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0039] In some alternative embodiments, the second time of the heat treatment is 30 - 60 min. For example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0040] As a preferred technical solution of the present invention, in step S4, the molar ratio of ammonium metavanadate to terephthalic acid is 1:1.5 - 2. For example, it can be 1:1.50, 1:1.55, 1:1.60, 1:1.65, 1:1.70, 1:1.75, 1:1.80, 1:1.85, 1:1.90, 1:1.95 or 1:2.00. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0041] In some alternative embodiments, the mixed solvent is N,N - dimethylformamide:ethanol:water with a volume ratio of 2:1:1;

[0042] In some alternative embodiments, the solid - liquid mass ratio of ammonium metavanadate and terephthalic acid to the mixed solvent is 1:15 - 20. For example, it can be 1:15.0, 1:15.5, 1:16.0, 1:16.5, 1:17.0, 1:17.5, 1:18.0, 1:18.5, 1:19.0, 1:19.5 or 1:20.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0043] In some alternative embodiments, the temperature of the hydrothermal reaction is 100 - 120 °C. For example, it can be 100 °C, 102 °C, 104 °C, 106 °C, 108 °C, 110 °C, 112 °C, 114 °C, 116 °C, 118 °C or 120 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0044] In some alternative embodiments, the time of the hydrothermal reaction is 18 - 20 h. For example, it can be 18.0 h, 18.2 h, 18.4 h, 18.6 h, 18.8 h, 19.0 h, 19.2 h, 19.4 h, 19.6 h, 19.8 h or 20.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0045] In some alternative embodiments, the temperature of heat treatment of the precursor substrate in an inert atmosphere is 300 - 400 °C. For example, it can be 300 °C, 310 °C, 320 °C, 330 °C, 340 °C, 350 °C, 360 °C, 370 °C, 380 °C, 390 °C or 400 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0046] In some alternative embodiments, the time of heat treatment of the precursor substrate in an inert atmosphere is 3 - 4 h. For example, it can be 3.0 h, 3.1 h, 3.2 h, 3.3 h, 3.4 h, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h or 4.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0047] In some alternative embodiments, the mass ratio of the metal - organic framework to lithium carbide is 1:0.3 - 0.5. For example, it can be 1:0.30, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.40, 1:0.42, 1:0.44, 1:0.46, 1:0.48 or 1:0.50. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0048] In some alternative embodiments, the solid - liquid mass ratio of the metal - organic framework and lithium carbide to tetrahydrofuran is 1:8 - 9. For example, it can be 1:8.0, 1:8.1, 1:8.2, 1:8.3, 1:8.4, 1:8.5, 1:8.6, 1:8.7, 1:8.8, 1:8.9 or 1:9.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0049] In some alternative embodiments, the temperature of heat treatment of the pretreated powder is 400 - 450 °C. For example, it can be 400 °C, 405 °C, 410 °C, 415 °C, 420 °C, 425 °C, 430 °C, 435 °C, 440 °C, 445 °C or 450 °C. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0050] In some alternative embodiments, the heat treatment time of the pretreated powder is 1 - 2 h. For example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0051] In some alternative embodiments, the mass ratio of the pre - lithium - inserted composite powder to polyacrylonitrile is 1:0.1 - 0.2. For example, it can be 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.20. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0052] In some alternative embodiments, the mass fraction of the N - methylpyrrolidone solution of polyacrylonitrile is 2 - 3 wt.%. For example, it can be 2.0 wt.%, 2.1 wt.%, 2.2 wt.%, 2.3 wt.%, 2.4 wt.%, 2.5 wt.%, 2.6 wt.%, 2.7 wt.%, 2.8 wt.%, 2.9 wt.% or 3.0 wt.%. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0053] In some alternative embodiments, the stirring reaction time of the reaction solution is 2 - 3 h. For example, it can be 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0054] As a preferred technical solution of the present invention, in step S5, during pre - dispersion, the solid - liquid mass ratio of the surface - coated metal - organic polymer, carboxymethyl cellulose to deionized water is 1:5 - 6. For example, it can be 1:5.0, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9 or 1:6.0. However, it is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.

[0055] In a second aspect, the present invention provides a long - cycle high - rate anode material. The long - cycle high - rate anode material includes a surface - coated metal - organic polymer, carboxymethyl cellulose, modified composite particles, a lithium - fluorocarbon additive and conductive carbon black.

[0056] In a third aspect, the present invention provides an application of a long-cycle high-rate anode material prepared by the above-mentioned preparation method in a lithium-ion battery.

[0057] In the present invention, silicon powder, tin powder and graphene are mixed, and a composite powder is prepared by a ball milling process. Silicon has become a research hotspot for anode materials due to its extremely high theoretical specific capacity. However, silicon undergoes significant volume expansion during charge and discharge processes. This volume change causes the active particles to gradually pulverize during repeated cycling and leads to interface stability problems. Specifically, the contact between the silicon surface and the electrolyte results in the repeated rupture and reconstruction of the solid electrolyte interface film, consuming a large amount of lithium ions and exacerbating the occurrence of side reactions, ultimately leading to rapid capacity decay. Therefore, it is difficult to meet the requirements of long-life cycling by using silicon alone as the anode material.

[0058] Tin is also a high-capacity material. Compared with silicon, its volume expansion problem is slightly smaller but still significant. In addition, the electrochemical performance of tin is easily limited by the increase in interface impedance. Especially under high-rate charge and discharge conditions, its interface chemical stability is poor, which further deteriorates the overall performance of the electrode. Generally speaking, although the expansion effect and interface stability problems of tin are easier to control than those of silicon, they still need to be optimized through composite design to achieve practical applications with long cycling and high rate.

[0059] To alleviate the structural stability problems of silicon and tin, the present invention uses graphene as a composite matrix. Graphene is a carbon material with high electrical conductivity and a two-dimensional sheet structure. With its large specific surface area and excellent mechanical flexibility, it plays a key role in the composite design. During the ball milling process, graphene can be evenly distributed between silicon and tin particles, forming a three-dimensional conductive network, significantly improving the overall electrical conductivity of the composite material. At the same time, graphene also serves as a flexible support framework, providing necessary mechanical buffering for silicon and tin to partially absorb the internal stress caused by their volume expansion, thereby slowing down the destruction of the material structure. In addition, the high specific surface area of graphene provides more intercalation and diffusion channels for lithium ions, helping to optimize the lithium ion transport path and reducing the polarization effect of the electrode.

[0060] After obtaining the silicon-tin-graphene composite powder, the present invention further conducts polyacrylonitrile carbonization coating modification on it to further improve the structural stability and interfacial properties of the composite material. During the high-temperature heat treatment process, polyacrylonitrile will undergo chemical conversion reactions such as dehydrogenation and denitrification, and finally form a carbon coating layer with a relatively low degree of graphitization. This carbon coating layer plays an important role in the composite particles. First of all, the carbon coating layer can provide effective mechanical constraints for silicon and tin particles, thereby inhibiting their volume expansion and maintaining the structural integrity of the composite particles. Secondly, as a medium for electron transport, the carbon layer and graphene jointly construct an efficient conductive network, significantly improving the electron transport ability of the composite material. Especially under high-rate charge and discharge conditions, it can significantly reduce the electrochemical polarization of the electrode. In addition, the carbon coating layer can also form a chemically stable protective barrier between the electrolyte and the active particles. This barrier effectively reduces the direct contact between the electrolyte and silicon and tin particles, thereby inhibiting the occurrence of side reactions on the material surface. At the same time, the carbon coating layer can stabilize the formation of the solid electrolyte interface film, reduce the rupture and reconstruction of the solid electrolyte interface film, and significantly reduce the irreversible capacity loss during the first charge and discharge.

[0061] Although the conductivity and structural stability of the composite material can be improved to a certain extent by compounding silicon and tin with graphene and further introducing a carbon coating layer, there are still some key problems to be solved. First of all, when the carbon coating layer is in direct contact with the electrolyte, uncontrollable side reactions may occur, resulting in the formation of an unstable solid electrolyte interface film. This unstable solid electrolyte interface film is prone to rupture and reformation during the charge and discharge process, not only consuming a large amount of lithium ions and electrolyte, increasing the irreversible capacity loss, but also further exacerbating the increase in interfacial impedance, which has a negative impact on the cycle life. Secondly, although the carbon coating layer alleviates the volume expansion problem of silicon and tin to a certain extent, due to the significant volume changes that silicon and tin still undergo during the charge and discharge process, poor contact may occur between local particles. This poor contact will damage the conductive network in the electrode, further restricting the rate performance and cycle stability of the material.

[0062] To solve the above problems and further optimize the performance of the composite material, the present invention introduces tungsten oxide as an interface stabilizer, and generates nano-scale tungsten oxide on the surface of carbon-coated particles through the calcination reaction of tungsten hexachloride. Tungsten oxide has high chemical stability and electrochemical activity, and its introduction can modify and optimize the composite material in multiple aspects. First, tungsten oxide forms a chemically stable inorganic protective layer on the surface of the negative electrode particles, which can effectively isolate the direct contact between the electrolyte and the active particles, thereby inhibiting the occurrence of side reactions and reducing the formation of an unstable solid electrolyte interface film. This protective layer can not only reduce the interfacial impedance on the electrode surface, but also significantly improve the interfacial chemical stability of the composite material. Second, tungsten oxide itself has a certain lithium-ion storage capacity. By participating in the insertion and extraction reactions of lithium ions during the electrochemical cycling process, tungsten oxide can provide additional lithium-ion storage sites, thereby enhancing the specific capacity of the negative electrode material. In addition, the rigidity and mechanical stability of tungsten oxide can play a certain mechanical constraint role on the volume expansion of silicon and tin during charge and discharge cycles, alleviating the problems of particle pulverization and poor contact.

[0063] It should be noted that the introduction of tungsten oxide may also enhance the interfacial bonding force between the composite particles. Between the carbon coating layer and graphene, tungsten oxide can further enhance the bonding strength between the particles through its good surface activity and mechanical stability, thereby improving the overall structural stability of the composite material. This enhanced interfacial bonding force helps to maintain the integrity of the conductive network, enabling the composite material to still maintain excellent performance under long cycling and high-rate conditions.

[0064] Through the synergistic effect among the high conductivity of graphene, the mechanical constraint ability of the carbon coating layer, and the surface stability of tungsten oxide, the performance of the composite material has been significantly optimized. Graphene and the carbon coating layer jointly construct an efficient electron transport network, significantly enhancing the overall conductivity of the material, especially showing excellent electron transport ability under high-rate charge and discharge conditions. At the same time, the introduction of tungsten oxide not only enhances the interfacial stability, but also further optimizes the structure and performance of the composite material through its lithium storage ability and mechanical support ability.

[0065] Secondly, to further improve the interfacial stability and electrochemical performance of the composite material, metaphosphoric acid and urea are introduced in the present invention for the second modification of the silicon-tin-graphene composite material. Metaphosphoric acid undergoes a decomposition reaction during high-temperature heat treatment, and its dissociation products can chemically react with the active sites on the surface of the composite particles to form inorganic phosphates with extremely high chemical stability. These inorganic phosphates form a uniform protective film on the material surface, which has multiple functions. First, the phosphate protective film has excellent chemical stability, which can effectively isolate the direct contact between the electrolyte and the active material (such as the surface of silicon, tin, or carbon), thus significantly reducing unnecessary side reactions, decreasing the decomposition rate of the electrolyte, and inhibiting the excessive growth of the solid electrolyte interface film. Secondly, the inorganic phosphate layer has a high lithium-ion conductivity, which enables lithium ions to quickly penetrate the protective film, thereby reducing the interfacial impedance and improving the electrochemical performance of the electrode. In addition, the inorganic rigid characteristics of the phosphate layer can play a certain mechanical support role during the volume expansion process of the material. This support effect can alleviate the structural damage caused by the expansion of silicon and tin, thereby further enhancing the cycling stability of the composite material.

[0066] Meanwhile, the introduction of urea provides an additional boost to the conductivity and interfacial activity of the material. Under high-temperature conditions, urea decomposes to release ammonia and carbon dioxide, and its decomposition products can chemically react with the carbon materials in the surrounding environment to form nitrogen-doped carbon-based materials. The nitrogen-doped carbon-based materials have significantly improved electronic structures. The introduction of nitrogen atoms changes the electron distribution in the carbon materials, resulting in a significant improvement in the conductivity of the carbon layer. In addition, nitrogen doping introduces more chemical active sites on the material surface. These active sites can not only promote the adsorption and storage of lithium ions but also enhance the rate performance and specific capacity performance of the material. More importantly, the nitrogen-doped carbon-based materials can stabilize the formation process of the solid electrolyte interface film at the interface between the electrolyte and the active particles. This stable solid electrolyte interface film has a low impedance and high mechanical integrity, thus effectively inhibiting the side reactions caused by the repeated rupture and reformation of the solid electrolyte interface film and further reducing the irreversible capacity loss of the battery.

[0067] The dual modification of metaphosphoric acid and urea forms a synergistic effect on interfacial chemistry and structural stability. The phosphate protective film generated by metaphosphoric acid provides a chemical barrier and mechanical support for the composite particles, while the nitrogen-doped carbon generated by urea not only enhances the conductivity of the material but also further optimizes the comprehensive performance of the composite material by improving the interfacial stability and lithium storage capacity. This second modification method significantly improves the cycling life and rate performance of the composite material, while providing a more stable interface and structural foundation for subsequent functionalization treatments.

[0068] The present invention prepares a lithium fluorocarbon additive by reacting lithium carbide with vinylidene fluoride to improve problems such as low initial Coulombic efficiency, poor interfacial stability, and irreversible lithium ion loss in high-capacity anode materials. Lithium carbide is a lithium-containing compound with high chemical activity and can serve as a pre-insertion source of lithium ions to achieve staged release of lithium ions during the preparation and formation processes of anode materials.

[0069] Lithium carbide can partially react with anode powder (such as active components like silicon and tin) to form local lithiated compounds. Since silicon and tin consume a large amount of lithium ions to form alloy phases during the first lithium insertion process, through the pre-reaction mechanism of lithium carbide, part of the lithiation process can be completed in advance during the material preparation stage, thereby reducing the lithium ion loss of active particles during the first charge and discharge and improving the initial Coulombic efficiency of the battery. In addition, the unreacted lithium carbide can continue to release lithium ions during the battery formation stage. These lithium ions can further react with un-lithiated silicon and tin particles or directly participate in the electrochemical reaction, thereby compensating for the irreversible lithium loss during the first charge and discharge and further enhancing the actual capacity and efficiency of the battery.

[0070] Meanwhile, the reaction between lithium carbide and vinylidene fluoride generates lithium fluoride or a lithium-fluorine-carbon composite structure, and these chemical products form a uniform interfacial protective layer on the anode surface. Lithium fluoride has high chemical inertness and low interfacial impedance, and its presence at the anode-electrolyte interface can effectively inhibit the decomposition of the electrolyte and the occurrence of interfacial side reactions. This not only reduces the irreversible loss of lithium ions but also significantly decreases the interfacial impedance, providing a lower impedance path for the insertion and extraction of lithium ions, thereby optimizing the electrochemical performance of the anode material. In addition, this interfacial protective layer also has high mechanical stability and can provide a certain buffering effect when the silicon and tin particles undergo volume expansion, further stabilizing the structure of the composite material.

[0071] During the battery formation stage, the unreacted lithium carbide continues to react with electrolyte components, the anode material surface, and other possible chemical components to release additional lithium ions. These released lithium ions not only directly embed into the material to form a lithiated alloy but also can participate in the formation process of the solid electrolyte interface film, reducing the consumption of lithium ions by electrolyte decomposition, thereby improving the stability and uniformity of the solid electrolyte interface film. Through this mechanism of staged release of lithium ions, lithium carbide maximizes the utilization efficiency of lithium ions and effectively reduces the loss of lithium metal anodes or electrolyte lithium salts.

[0072] The present invention synthesizes a vanadium-based metal-organic framework through ammonium metavanadate and terephthalic acid under hydrothermal reaction conditions. Such metal-organic framework materials exhibit great application potential in the design of the negative electrode of lithium-ion batteries due to their unique high specific surface area and good ion channel structure. The porous structure of the metal-organic framework materials can not only provide abundant reactive sites for reactions, but also provide a low-impedance transport channel for the insertion and diffusion of lithium ions, thus significantly improving the electrochemical performance of the negative electrode materials.

[0073] During the preparation process, the metal-organic framework undergoes a chemical reaction with lithium carbide to achieve pre-lithiation modification of the metal-organic framework. Lithium carbide is a lithium-containing compound with relatively high chemical activity. After reacting with the metal-organic framework, it can introduce lithium ions into the material interior to generate a composite material with initial lithium ion activity. This pre-lithiation process provides an important lithium ion source for the first charge and discharge of the negative electrode material, thus significantly reducing the first irreversible capacity loss and improving the first Coulombic efficiency of the battery. In addition, the lithium-inserted metal-organic framework material can further release lithium ions during the battery formation stage, enabling the negative electrode material to have higher activity and lower lithium ion consumption during the first cycle.

[0074] It is worth noting that the high specific surface area and ordered ion channel structure of the metal-organic framework play a positive role in the pre-lithiation process. On the one hand, the high specific surface area provides more reactive sites for the insertion of lithium ions, making the lithium insertion process more efficient; on the other hand, the ion channel structure of the framework optimizes the diffusion path of lithium ions, significantly reducing the migration impedance of lithium ions within the material. This structural characteristic promotes the rapid transport of lithium ions during subsequent cycling processes, thus improving the rate performance of the battery. In addition, the porous structure of the metal-organic framework can also buffer the stress generated during the volume expansion of active particles such as silicon and tin, effectively enhancing the mechanical stability of the composite material.

[0075] In order to further enhance the electrical conductivity and structural stability of the metal-organic framework, the present invention also introduces a graphitized carbon coating layer on its surface. Polyacrylonitrile is used as a carbon source and undergoes chemical reactions such as dehydrogenation and denitrification during high-temperature heat treatment to finally form a uniform graphitized carbon layer. This carbon coating layer plays multiple functions in the structure of the metal-organic framework. First of all, the graphitized carbon layer has high electrical conductivity and jointly constructs an efficient electron transport network with the metal-organic framework, greatly improving the overall electrical conductivity of the composite material. Secondly, the mechanical stability of the carbon layer can further enhance the structural integrity of the metal-organic framework, providing guarantee for the stability of the material during long-term cycling. In addition, the carbon layer can also form a chemical protection barrier on the surface of the negative electrode, reducing the direct contact between the electrolyte and the active particles, thereby inhibiting the occurrence of side reactions and further stabilizing the formation of the solid electrolyte interface film.

[0076] Multiple optimizations of the anode material are achieved by combining the high specific surface area and ion channel structure of metal-organic frameworks with the pre-lithiation process of lithium carbide. The lithiated metal-organic frameworks not only provide an additional lithium ion source for the anode but also improve the rate performance and cycling stability of the material by optimizing the lithium ion diffusion path and the distribution of active sites. Meanwhile, the surface graphitized carbon coating further enhances the electronic conductivity and structural stability of the composite material.

[0077] There is also a synergistic enhancement effect in the present invention. The synergistic effect between metal-organic frameworks and lithium carbide in the material preparation process is mainly reflected in the pre-embedding and diffusion optimization of lithium ions. Metal-organic framework materials have a high specific surface area and an ordered ion channel structure, providing a large number of active sites and low-impedance paths for the embedding and transport of lithium ions. During the reaction with lithium carbide, these structural characteristics maximize the lithium ion embedding efficiency. In addition, the structural characteristics of metal-organic framework materials can buffer the volume stress that may occur during the lithiation process, prevent mechanical damage to the material, and ensure the uniform progress of the lithiation reaction. The staged lithium ion release function of lithium carbide further matches the high active sites of metal-organic frameworks, making the lithium ion storage and release processes more uniform and efficient. This synergistic effect significantly reduces the irreversible lithium loss during the first charge and discharge and improves the first Coulombic efficiency of the material.

[0078] The synergistic effect between metal-organic frameworks and the graphitized carbon coating is mainly reflected in the improvement of conductivity and the enhancement of structural stability. The conductivity of metal-organic framework materials themselves is relatively low, but after being coated with a layer of graphitized carbon on their surface, the electron transport performance can be significantly improved. The graphitized carbon layer not only provides an efficient electron transport channel for metal-organic frameworks but also synergistically acts with the porous structure of metal-organic frameworks to provide a faster transport path for the embedding and diffusion of lithium ions. In addition, the mechanical flexibility of the graphitized carbon layer can further enhance the overall structural stability of metal-organic frameworks, effectively alleviating the internal stress caused by the volume expansion of silicon or tin particles during cycling, thereby inhibiting the pulverization of particles and the collapse of the electrode structure.

[0079] There is also a significant synergistic effect between the prelithiation process of lithium carbide and the graphitized carbon coating layer. The lithium ions released by lithium carbide during the reaction can directly participate in the lithiation of the metal-organic framework, and at the same time, stable lithium compounds (such as lithium fluoride or lithiated carbon) may be formed on the surface of the graphitized carbon layer. The interfacial layer formed by these lithium compounds on the electrode surface has high chemical stability and low impedance characteristics, which can further optimize the interfacial stability between the negative electrode and the electrolyte. In addition, the conductivity of the graphitized carbon layer provides a more efficient electron channel for the transport of lithium ions released by lithium carbide, thus promoting the uniform embedding of lithium ions. This synergistic effect improves both the interfacial performance and the electrochemical activity of the electrode.

[0080] As high-capacity negative electrode materials, the significant volume expansion during the charge and discharge processes of silicon and tin is one of the main problems to be solved. The combined action of the porous structure of the metal-organic framework and the mechanical flexibility of the graphitized carbon layer provides a good expansion buffer space for silicon and tin particles. The porosity of the metal-organic framework enables the expanded silicon or tin particles to be constrained within the framework, while the graphitized carbon layer further enhances this buffering ability through mechanical support. This synergistic effect significantly improves the cycle stability of the material and extends the service life of the battery.

[0081] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0082] By compounding silicon powder, tin powder with graphene and using polyacrylonitrile carbonization coating, a three-dimensional conductive network is constructed to optimize the lithium ion transport path, while alleviating the volume expansion and interfacial stability problems of silicon and tin. The carbon coating layer further enhances the mechanical constraint, stabilizes the interface, reduces side reactions and irreversible capacity loss. The synergistic effect between graphene and the carbon layer significantly improves the conductivity, cycle stability and rate performance of the material;

[0083] By introducing tungsten oxide as an interface stabilizer to form a stable protective layer, side reactions are inhibited, the interfacial impedance is reduced, and the specific capacity is increased by utilizing its lithium storage capacity. At the same time, tungsten oxide alleviates the volume expansion of silicon and tin and enhances the integrity of the conductive network. The synergistic effect of the high conductivity of graphene, the mechanical constraint of the carbon coating layer and the interfacial stability of tungsten oxide endows the material with excellent electrochemical performance and structural stability;

[0084] Metaphosphoric acid decomposes to form an inorganic phosphate protective film, isolating the electrolyte from contact with the active material, inhibiting side reactions and the excessive growth of the solid electrolyte interface film, while providing mechanical support to alleviate the volume expansion problem. Urea decomposes to form nitrogen-doped carbon, significantly improving the conductivity and interfacial activity of the material and stabilizing the solid electrolyte interface film, reducing side reactions and irreversible capacity loss. The synergistic effect of the two significantly enhances the interfacial stability and electrochemical performance, improving the cycle life, rate performance and structural stability;

[0085] The lithium-fluorocarbon additive is prepared by reacting lithium carbide with vinylidene fluoride, which can improve the first Coulombic efficiency and actual capacity of the anode material. As a lithium ion pre-insertion source, lithium carbide releases lithium ions in stages, reducing the first lithium loss. Meanwhile, the lithium fluoride or lithium-fluorocarbon composite protective layer reduces the interfacial impedance, inhibits side reactions and provides mechanical buffering, enhancing the structural stability. During the formation stage, the unreacted lithium carbide continues to release lithium ions, promoting the uniform formation of the solid electrolyte interface film and further optimizing the electrochemical performance and stability;

[0086] Vanadium-based metal-organic frameworks are prepared by the hydrothermal reaction of ammonium metavanadate and terephthalic acid, and pre-lithiated modification is carried out using lithium carbide, while a graphitized carbon coating layer is introduced. The high specific surface area and ordered ion channels of the metal-organic frameworks optimize the lithium ion transport path, improving the first Coulombic efficiency and rate performance. Pre-lithiation reduces irreversible capacity loss, and the porous structure alleviates volume expansion, enhancing mechanical stability. The graphitized carbon coating layer further improves the conductivity, structural integrity and inhibits side reactions, significantly optimizing the cycle stability and electrochemical performance of the anode material. Brief Description of the Drawings

[0087] Figure 1 It is a flowchart of the preparation method of the long-cycle high-rate anode material provided in Embodiment 1 of the present invention. Detailed Embodiments

[0088] The technical solution of the present invention will be described in detail below with reference to specific embodiments and their accompanying drawings. The embodiments described herein are specific specific embodiments of the present invention for explaining the concept of the present invention; these descriptions are all explanatory and exemplary, and should not be construed as limiting the embodiments of the present invention and the protection scope of the present invention. Except for the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application, and these technical solutions include technical solutions that make any obvious substitutions and modifications to the embodiments described herein.

[0089] The chemical reagents used in the embodiments and comparative examples of the present invention are all commercially available products and have not been further purified or treated.

[0090] Embodiment 1

[0091] This embodiment provides a long-cycle high-rate anode material and its preparation method. The preparation method specifically includes the following steps:

[0092] S1: Mix silicon powder, tin powder and graphene by ball milling to obtain a composite powder; react it with polyacrylonitrile in N-methylpyrrolidone, dry and then heat-treat to obtain carbon-coated composite particles; impregnate and react it with an ethanol solution of tungsten hexachloride and calcine to obtain the first modified carbon-coated composite particles;

[0093] Specifically, S1: Mix silicon powder, tin powder, and graphene and then ball-mill to obtain a composite powder. The mass ratio of silicon powder to graphene is 3.6:1, and the mass ratio of tin powder to graphene is 2.7:1. Add it and polyacrylonitrile to N-methylpyrrolidone and stir to coat. The mass ratio of the composite powder to polyacrylonitrile is 1:4.1, and the solid-liquid mass ratio of the composite powder and polyacrylonitrile to N-methylpyrrolidone is 1:3.8. After drying, heat-treat at 530 °C for 2 h in an inert atmosphere to obtain carbon-coated composite particles; Immerse it in an ethanol solution of tungsten hexachloride with a concentration of 0.08 M for impregnation reaction. The mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:10, and calcine at 520 °C for 2 h to obtain the first modified carbon-coated composite particles;

[0094] S2: Mix the first modified carbon-coated composite particles with metaphosphoric acid and urea in absolute ethanol, dry and then heat-treat to obtain modified composite particles;

[0095] Specifically, S2: Mix the first modified carbon-coated composite particles with metaphosphoric acid and urea and then uniformly disperse them in absolute ethanol. The mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:9, and the mass ratio of the first modified carbon-coated composite particles to urea is 100:8. The solid-liquid mass ratio of the first modified carbon-coated composite particles, metaphosphoric acid, and urea to absolute ethanol is 1:5.7. After reaction and drying, place it in an inert atmosphere and heat-treat at 400 °C for 2.4 h to obtain modified composite particles;

[0096] S3: React lithium carbide with polyvinylidene fluoride in tetrahydrofuran, dry and then heat-treat to obtain a lithium-fluorocarbon additive;

[0097] Specifically, S3: Disperse lithium carbide and polyvinylidene fluoride in tetrahydrofuran at a mass ratio of 1:1.6. The solid-liquid mass ratio of lithium carbide and polyvinylidene fluoride to tetrahydrofuran is 1:9.4. Stir and react for 2 h, then dry. Subsequently, heat-treat at 250 °C for 1 h in an inert atmosphere and then raise the temperature to 400 °C for 30 min to obtain a lithium-fluorocarbon additive;

[0098] S4: Hydrothermally react ammonium metavanadate with terephthalic acid and then heat-treat to obtain a metal-organic framework; React it with lithium carbide in tetrahydrofuran and heat-treat to obtain a pre-lithiated composite powder, and react it with polyacrylonitrile to obtain a surface-coated metal-organic polymer;

[0099] Specifically, S4: Ammonium metavanadate and terephthalic acid are added to a mixed solvent at a molar ratio of 1:1.8, where the solid-liquid mass ratio of ammonium metavanadate and terephthalic acid to the mixed solvent is 1:18, and the volume ratio of N,N-dimethylformamide, ethanol, and deionized water in the mixed solvent is 2:1:1. After hydrothermal reaction at 100 °C for 18 h, filtration, washing, and drying are carried out to obtain a precursor substrate, which is heat-treated at 300 °C for 3 h in an inert atmosphere to obtain a metal-organic framework; it is dispersed with lithium carbide in tetrahydrofuran at a mass ratio of 1:0.4, where the solid-liquid mass ratio of the metal-organic framework and lithium carbide to tetrahydrofuran is 1:8.7. After stirring and reacting, drying is carried out to obtain a pretreated powder, which is heat-treated at 400 °C for 1 h to obtain a pre-lithiated composite powder; in an inert atmosphere, the pre-lithiated composite powder is dispersed in an N-methylpyrrolidone solution of polyacrylonitrile with a mass fraction of 2 wt.%, where the mass ratio of the pre-lithiated composite powder to polyacrylonitrile is 1:0.16. After stirring and reacting for 2 h, rotary evaporation is carried out to obtain a surface-coated metal-organic polymer;

[0100] S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed, and modified composite particles, lithium fluorocarbon additive, and conductive carbon black are added to prepare a long-cycle high-rate anode material.

[0101] Specifically, S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed in deionized water to obtain a pretreated base liquid, where the solid-liquid mass ratio of the surface-coated metal-organic polymer and carboxymethyl cellulose to deionized water is 1:5.7. Subsequently, modified composite particles and lithium fluorocarbon additive are added. After uniform dispersion, conductive carbon black is added, and defoaming is carried out to obtain a long-cycle high-rate anode material, where the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 4.3:4.2:78:3.6:4.

[0102] Example 2

[0103] This example provides a long-cycle high-rate anode material and a preparation method thereof. The preparation method specifically includes the following steps:

[0104] S1: Silicon powder, tin powder, and graphene are mixed and ball-milled to obtain a composite powder; it is reacted with polyacrylonitrile in N-methylpyrrolidone, and after drying, heat treatment is carried out to obtain carbon-coated composite particles; it is impregnated and reacted with an ethanol solution of tungsten hexachloride and calcined to obtain first modified carbon-coated composite particles;

[0105] Specifically, S1: Mix silicon powder, tin powder and graphene and then ball-mill them to obtain a composite powder. The mass ratio of silicon powder to graphene is 4:1, and the mass ratio of tin powder to graphene is 3:1. Add it and polyacrylonitrile to N-methylpyrrolidone and stir to coat them. The mass ratio of the composite powder to polyacrylonitrile is 1:5, and the solid-liquid mass ratio of the composite powder and polyacrylonitrile to N-methylpyrrolidone is 1:4.5. After drying, heat-treat it in an inert atmosphere at 600 °C for 3 h to obtain carbon-coated composite particles; Immerse them in an ethanol solution of tungsten hexachloride with a concentration of 0.05 M for impregnation reaction. The mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:11, and calcine them at 550 °C for 2.5 h to obtain the first modified carbon-coated composite particles;

[0106] S2: Mix the first modified carbon-coated composite particles with metaphosphoric acid and urea in absolute ethanol, and heat-treat them after drying to obtain modified composite particles;

[0107] Specifically, S2: Uniformly disperse the first modified carbon-coated composite particles, metaphosphoric acid and urea in absolute ethanol. The mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:9.6, and the mass ratio of the first modified carbon-coated composite particles to urea is 100:9. The solid-liquid mass ratio of the first modified carbon-coated composite particles, metaphosphoric acid and urea to absolute ethanol is 1:6. After reaction and drying, place them in an inert atmosphere and heat-treat them at 420 °C for 2 h to obtain modified composite particles;

[0108] S3: React lithium carbide with polyvinylidene fluoride in tetrahydrofuran, and heat-treat them after drying to obtain a lithium fluorocarbon additive;

[0109] Specifically, S3: Disperse lithium carbide and polyvinylidene fluoride in tetrahydrofuran at a mass ratio of 1:2. The solid-liquid mass ratio of lithium carbide and polyvinylidene fluoride to tetrahydrofuran is 1:9.8. Stir and react for 2.6 h and then dry. Subsequently, heat-treat them in an inert atmosphere at 270 °C for 2 h and then raise the temperature to 440 °C for 50 min to obtain a lithium fluorocarbon additive;

[0110] S4: Hydrothermally react ammonium metavanadate with terephthalic acid and then heat-treat them to obtain a metal-organic framework; React it with lithium carbide in tetrahydrofuran and heat-treat to obtain a pre-lithiated composite powder, and react it with polyacrylonitrile to obtain a surface-coated metal-organic polymer;

[0111] Specifically, S4: Ammonium metavanadate and terephthalic acid are added to a mixed solvent at a molar ratio of 1:1.7, where the solid-liquid mass ratio of ammonium metavanadate and terephthalic acid to the mixed solvent is 1:20. The volume ratio of N,N-dimethylformamide, ethanol, and deionized water in the mixed solvent is 2:1:1. After hydrothermal reaction at 110 °C for 19 h, filtration, washing, and drying are carried out to obtain a precursor substrate, which is heat-treated at 350 °C for 3.6 h in an inert atmosphere to obtain a metal-organic framework; it is dispersed with lithium carbide in tetrahydrofuran at a mass ratio of 1:0.5, where the solid-liquid mass ratio of the metal-organic framework and lithium carbide to tetrahydrofuran is 1:9. After stirring reaction and drying, a pretreated powder is obtained, and heat treatment at 430 °C for 1.6 h gives a pre-lithiated composite powder; in an inert atmosphere, the pre-lithiated composite powder is dispersed in an N-methylpyrrolidone solution of polyacrylonitrile with a mass fraction of 2.7 wt.%, where the mass ratio of the pre-lithiated composite powder to polyacrylonitrile is 1:0.2. After stirring reaction for 3 h, rotary evaporation gives a surface-coated metal-organic polymer;

[0112] S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed, and modified composite particles, lithium fluorocarbon additive, and conductive carbon black are added to prepare a long-cycle high-rate anode material.

[0113] Specifically, S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed in deionized water to obtain a pretreated base liquid, where the solid-liquid mass ratio of the surface-coated metal-organic polymer and carboxymethyl cellulose to deionized water is 1:6. Subsequently, modified composite particles and lithium fluorocarbon additive are added. After uniform dispersion, conductive carbon black is added, and defoaming gives a long-cycle high-rate anode material, where the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 4:5:77:3:3.

[0114] Example 3

[0115] This example provides a long-cycle high-rate anode material and a preparation method thereof. The preparation method specifically includes the following steps:

[0116] S1: Silicon powder, tin powder, and graphene are mixed and ball-milled to obtain a composite powder; it is reacted with polyacrylonitrile in N-methylpyrrolidone, and after drying, heat treatment gives a carbon-coated composite particle; it is impregnated and reacted with an ethanol solution of tungsten hexachloride and calcined to obtain a first modified carbon-coated composite particle;

[0117] Specifically, S1: Mix silicon powder, tin powder, and graphene and then ball-mill them to obtain a composite powder. The mass ratio of silicon powder to graphene is 3:1, and the mass ratio of tin powder to graphene is 2:1. Add it and polyacrylonitrile to N-methylpyrrolidone and stir to coat them. The mass ratio of the composite powder to polyacrylonitrile is 1:3, and the solid-liquid mass ratio of the composite powder and polyacrylonitrile to N-methylpyrrolidone is 1:3. After drying, heat-treat it in an inert atmosphere at 500 °C for 3.5 h to obtain carbon-coated composite particles; Immerse them in an ethanol solution of tungsten hexachloride with a concentration of 0.07 M for impregnation reaction. The mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:8, and calcine them at 500 °C for 2.8 h to obtain the first modified carbon-coated composite particles;

[0118] S2: Mix the first modified carbon-coated composite particles, metaphosphoric acid, and urea in absolute ethanol, and heat-treat them after drying to obtain modified composite particles;

[0119] Specifically, S2: Uniformly disperse the first modified carbon-coated composite particles, metaphosphoric acid, and urea in absolute ethanol. The mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:8, and the mass ratio of the first modified carbon-coated composite particles to urea is 100:10. The solid-liquid mass ratio of the first modified carbon-coated composite particles, metaphosphoric acid, and urea to absolute ethanol is 1:5. After reaction and drying, place them in an inert atmosphere and heat-treat them at 430 °C for 2.7 h to obtain modified composite particles;

[0120] S3: React lithium carbide with polyvinylidene fluoride in tetrahydrofuran, and heat-treat them after drying to obtain a lithium fluorocarbon additive;

[0121] Specifically, S3: Disperse lithium carbide and polyvinylidene fluoride in tetrahydrofuran at a mass ratio of 1:1. The solid-liquid mass ratio of lithium carbide and polyvinylidene fluoride to tetrahydrofuran is 1:9. Stir and react for 2.8 h and then dry. Subsequently, heat-treat them in an inert atmosphere at 260 °C for 1.2 h and then raise the temperature to 430 °C for 45 min to obtain a lithium fluorocarbon additive;

[0122] S4: Hydrothermally react ammonium metavanadate with terephthalic acid and then heat-treat it to obtain a metal-organic framework; React it with lithium carbide in tetrahydrofuran and heat-treat it to obtain a pre-lithiated composite powder, and react it with polyacrylonitrile to obtain a surface-coated metal-organic polymer;

[0123] Specifically, S4: Ammonium metavanadate and terephthalic acid are added to a mixed solvent at a molar ratio of 1:1.5, where the solid-liquid mass ratio of ammonium metavanadate and terephthalic acid to the mixed solvent is 1:15, and the volume ratio of N,N-dimethylformamide, ethanol, and deionized water in the mixed solvent is 2:1:1. Hydrothermal reaction is carried out at 115 °C for 18.5 h, followed by filtration, washing, and drying to obtain a precursor substrate. It is heat-treated at 380 °C for 3.8 h in an inert atmosphere to obtain a metal-organic framework; it is dispersed with lithium carbide in tetrahydrofuran at a mass ratio of 1:0.3, where the solid-liquid mass ratio of the metal-organic framework and lithium carbide to tetrahydrofuran is 1:8.3. After stirring reaction and drying, a pretreated powder is obtained, and it is heat-treated at 420 °C for 1.8 h to obtain a pre-lithiated composite powder; in an inert atmosphere, the pre-lithiated composite powder is dispersed in an N-methylpyrrolidone solution of polyacrylonitrile with a mass fraction of 2.4 wt.%, where the mass ratio of the pre-lithiated composite powder to polyacrylonitrile is 1:0.1. After stirring reaction for 2.3 h, rotary evaporation is carried out to obtain a surface-coated metal-organic polymer;

[0124] S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed, and modified composite particles, lithium fluorocarbon additive, and conductive carbon black are added to prepare a long-cycle high-rate anode material.

[0125] Specifically, S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed in deionized water to obtain a pretreated base liquid, where the solid-liquid mass ratio of the surface-coated metal-organic polymer and carboxymethyl cellulose to deionized water is 1:5. Subsequently, modified composite particles and lithium fluorocarbon additive are added. After uniform dispersion, conductive carbon black is added, and defoaming is carried out to obtain a long-cycle high-rate anode material, where the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 4.7:4.5:75:3.8:3.7.

[0126] Example 4

[0127] This example provides a long-cycle high-rate anode material and a preparation method thereof. The preparation method specifically includes the following steps:

[0128] S1: Silicon powder, tin powder, and graphene are mixed and ball-milled to obtain a composite powder; it is reacted with polyacrylonitrile in N-methylpyrrolidone, and after drying, heat treatment is carried out to obtain carbon-coated composite particles; it is impregnated and reacted with an ethanol solution of tungsten hexachloride and calcined to obtain first modified carbon-coated composite particles;

[0129] Specifically, S1: Mix silicon powder, tin powder and graphene and then ball-mill to obtain a composite powder. The mass ratio of silicon powder to graphene is 3.4:1, and the mass ratio of tin powder to graphene is 2.3:1. Add it and polyacrylonitrile to N-methylpyrrolidone and stir to coat. The mass ratio of the composite powder to polyacrylonitrile is 1:4.5, and the solid-liquid mass ratio of the composite powder and polyacrylonitrile to N-methylpyrrolidone is 1:5. After drying, heat-treat at 580 °C for 4 h in an inert atmosphere to obtain carbon-coated composite particles; Immerse them in an ethanol solution of tungsten hexachloride with a concentration of 0.1 M for impregnation reaction. The mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:12, and calcine at 530 °C for 3 h to obtain the first modified carbon-coated composite particles;

[0130] S2: Mix the first modified carbon-coated composite particles with metaphosphoric acid and urea in absolute ethanol, dry and then heat-treat to obtain modified composite particles;

[0131] Specifically, S2: Disperse the first modified carbon-coated composite particles, metaphosphoric acid and urea evenly in absolute ethanol. The mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:10, and the mass ratio of the first modified carbon-coated composite particles to urea is 100:9.4. The solid-liquid mass ratio of the first modified carbon-coated composite particles, metaphosphoric acid and urea to absolute ethanol is 1:5.3. React, dry and then place in an inert atmosphere and heat-treat at 450 °C for 3 h to obtain modified composite particles;

[0132] S3: React lithium carbide with polyvinylidene fluoride in tetrahydrofuran, dry and then heat-treat to obtain a lithium fluorocarbon additive;

[0133] Specifically, S3: Disperse lithium carbide and polyvinylidene fluoride in tetrahydrofuran at a mass ratio of 1:1.2. The solid-liquid mass ratio of lithium carbide and polyvinylidene fluoride to tetrahydrofuran is 1:10. Stir and react for 3 h and then dry. Subsequently, heat-treat at 280 °C for 1.7 h in an inert atmosphere and then raise the temperature to 450 °C for 60 min to obtain a lithium fluorocarbon additive;

[0134] S4: Hydrothermally react ammonium metavanadate with terephthalic acid and then heat-treat to obtain a metal-organic framework; React it with lithium carbide in tetrahydrofuran and heat-treat to obtain a pre-lithiated composite powder, and react it with polyacrylonitrile to obtain a surface-coated metal-organic polymer;

[0135] Specifically, S4: Ammonium metavanadate and terephthalic acid are added to a mixed solvent at a molar ratio of 1:2, where the solid-liquid mass ratio of ammonium metavanadate and terephthalic acid to the mixed solvent is 1:16, and the volume ratio of N,N-dimethylformamide, ethanol, and deionized water in the mixed solvent is 2:1:1. After hydrothermal reaction at 120 °C for 20 h, filtration, washing, and drying are carried out to obtain a precursor substrate, which is heat-treated at 400 °C for 4 h in an inert atmosphere to obtain a metal-organic framework; it is dispersed with lithium carbide at a mass ratio of 1:0.45 in tetrahydrofuran, where the solid-liquid mass ratio of the metal-organic framework and lithium carbide to tetrahydrofuran is 1:8. After stirring reaction and drying, a pretreated powder is obtained, and it is heat-treated at 450 °C for 2 h to obtain a pre-lithiated composite powder; in an inert atmosphere, the pre-lithiated composite powder is dispersed in an N-methylpyrrolidone solution of polyacrylonitrile with a mass fraction of 3 wt.%, where the mass ratio of the pre-lithiated composite powder to polyacrylonitrile is 1:0.12. After stirring reaction for 2.7 h, rotary evaporation is carried out to obtain a surface-coated metal-organic polymer;

[0136] S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed, and modified composite particles, lithium fluorocarbon additive, and conductive carbon black are added to prepare a long-cycle high-rate anode material.

[0137] Specifically, S5: The surface-coated metal-organic polymer and carboxymethyl cellulose are pre-dispersed in deionized water to obtain a pretreated base liquid, where the solid-liquid mass ratio of the surface-coated metal-organic polymer and carboxymethyl cellulose to deionized water is 1:5.3. Subsequently, modified composite particles and lithium fluorocarbon additive are added. After uniform dispersion, conductive carbon black is added, and defoaming is carried out to obtain a long-cycle high-rate anode material, where the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 5:4:80:4:5.

[0138] Comparative Example 1

[0139] This comparative example provides a long-cycle high-rate anode material. The difference from Example 1 is that in S1, the mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:15, and the other operation steps and process parameters are exactly the same as those in Example 1.

[0140] Comparative Example 2

[0141] This comparative example provides a long-cycle high-rate anode material. The difference from Example 1 is that in S1, the mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:5, and the other operation steps and process parameters are exactly the same as those in Example 1.

[0142] Comparative Example 3

[0143] This comparative example provides a long-cycle high-rate anode material, which is different from that of Example 1 in that in S5, the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 8:4.2:78:3.6:4, and other operation steps and process parameters are exactly the same as those of Example 1.

[0144] Comparative Example 4

[0145] This comparative example provides a long-cycle high-rate anode material, which is different from that of Example 1 in that in S5, the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 2:4.2:78:3.6:4, and other operation steps and process parameters are exactly the same as those of Example 1.

[0146] Comparative Example 5

[0147] This comparative example provides a long-cycle high-rate anode material, which is different from that of Example 1 in that in S5, the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 2:4.2:78:5:4, and other operation steps and process parameters are exactly the same as those of Example 1.

[0148] Comparative Example 6

[0149] This comparative example provides a long-cycle high-rate anode material, which is different from that of Example 1 in that in S5, the mass ratio of the surface-coated metal-organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive, and conductive carbon black is 2:4.2:78:1:4, and other operation steps and process parameters are exactly the same as those of Example 1.

[0150] Perform performance tests on the long-cycle high-rate anode materials of the above Examples 1-4 and Comparative Examples 1-6. The specific process is as follows:

[0151] Uniformly coat the prepared anode material on a copper foil, and use it as a working electrode after vacuum drying. Use metallic lithium as the counter electrode, a polypropylene microporous membrane as the separator, and a 1M LiPF6 / DMC:EC:DEC = 1:1:1 solution as the electrolyte to assemble a simulated battery.

[0152] At 25 °C, the simulated battery is first charged at a constant current of 1C to 4.3V, further charged at a constant voltage of 4.3V until the current is 0.025C, and then discharged at a constant current of 1C to 3.0V. This is a charge-discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. Perform multiple cycle charge-discharge tests in the above manner to detect the discharge capacity of the 500th cycle;

[0153] Capacity retention rate (%) after 500 battery cycles = [Discharge capacity at the 500th cycle / Discharge capacity at the 1st cycle] × 100%.

[0154] High-rate performance test:

[0155] At 25 °C, the simulated battery is charged at a constant current of 1C to 4.3V, and then charged at a constant voltage of 4.3V until the current reaches 0.025C. Subsequently, it is discharged at a high rate (5C, 10C, 20C) at a constant current to 3.0V, and the discharge capacities under different rate conditions are recorded.

[0156] High-rate capacity retention rate of the simulated battery = [Discharge capacity at high rate / Discharge capacity at 1C rate] × 100%.

[0157] The test results are shown in Table 1.

[0158] Table 1: Test results of long-cycle high-rate anode materials for Examples 1-4 and Comparative Examples 1-6

[0159]

[0160] From the test results of Example 1 and Comparative Examples 1 and 2, when the mass ratio of the carbon-coated composite particles to tungsten hexachloride is too low, excessive tungsten oxide will accumulate on the surface of the composite particles, forming an unevenly thick agglomerated layer, resulting in a decrease in the first charge-discharge capacity to 564 mAh / g; at the same time, due to the increase in the interfacial transfer impedance, the cycle capacity retention rate of the battery drops to 65.75%, and the rate performance also decays; while when the mass ratio is too high, the tungsten oxide protective layer is not completely covered, causing the active material to be directly exposed to the electrolyte. Although the first discharge capacity can reach 787 mAh / g, continuous side reactions at the interface lead to a decrease in the cycle capacity retention rate of the battery to 70.31%, and the rate performance also deteriorates;

[0161] From the test results of Example 1 and Comparative Examples 3 and 4, when the content of the surface-coated metal-organic polymer is too high, although the excessive MOF layer provides rich ion migration channels, it also prolongs the actual transmission path of lithium ions and reduces the relative content of the active material. The first discharge capacity drops to 743 mAh / g, and due to the increase in the lithium ion transmission path, the cycle capacity retention rate of the battery drops to 75.75%, and the high-rate performance is not good; while when the content is too low, due to insufficient ion channels and active sites provided by the MOF, the pre-lithiation effect weakens, and the volume expansion stress of tin and silicon cannot be effectively buffered, resulting in a first discharge capacity of 840 mAh / g, but the cycle capacity retention rate of the battery decays to 68.65%, and the high-rate performance also deteriorates;

[0162] From the test results of Example 1 and Comparative Example 5 and Comparative Example 6, it can be seen that when the content of lithium fluorocarbon additive is too high, excessive lithium fluoride forms a dense passivation layer, which hinders the lithium ion transport. The initial charge-discharge capacity drops to 768 mAh / g, and the cycle capacity retention rate drops to 75.38%. When the content is too low, the interface regulation effect is insufficient. Although the initial discharge capacity reaches 800 mAh / g, the poor stability of the solid electrolyte interface film leads to the attenuation of the battery cycle capacity and the decline of the high-rate performance.

[0163] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived within the technical scope disclosed by the present invention by those skilled in the art all fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A method for preparing a long cycle high rate negative electrode material, characterized in that: The preparation method comprises: S1: mixing silicon powder, tin powder and graphene and ball-milling to obtain composite powder; reacting the powder with polyacrylonitrile in N-methylpyrrolidone, drying and heat-treating the mixture to obtain carbon-coated composite particles; impregnating the mixture with an ethanol solution of tungsten hexachloride and reacting the mixture, and calcining the mixture to obtain first modified carbon-coated composite particles; S2: mixing the first modified carbon-coated composite particles with metaphosphoric acid and urea in anhydrous ethanol, drying and heat-treating to obtain modified composite particles; S3: reacting lithium carbide with vinylidene fluoride in tetrahydrofuran, drying and heat-treating to obtain a lithium fluorocarbon additive; S4: hydrothermally reacting ammonium metavanadate with terephthalic acid and then subjecting it to heat treatment to obtain a metal-organic framework; subjecting it to a reaction with lithium carbide in tetrahydrofuran and subjecting it to heat treatment to obtain a pre-embedded lithium composite powder; and subjecting it to a reaction with polyacrylonitrile to obtain a surface-coated metal-organic polymer; S5: The surface-coated metal-organic polymer is pre-dispersed with carboxymethyl cellulose, and modified composite particles, lithium fluorocarbon additives and conductive carbon black are added to prepare a long-cycle and high-rate negative electrode material.

2. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S1: The mass ratio of silicon powder to graphene is 3-4:1; The mass ratio of the tin powder to the graphene is 2-3:1; The mass ratio of the composite powder to polyacrylonitrile is 1:3-5; The solid-liquid mass ratio of the composite powder to polyacrylonitrile and N-methylpyrrolidone is 1:3-5.

3. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S1: The concentration of the ethanol solution of tungsten hexachloride is 0.05-0.1M; The mass ratio of the carbon-coated composite particles to tungsten hexachloride is 100:8-12.

4. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S2: The mass ratio of the first modified carbon-coated composite particles to metaphosphoric acid is 100:8-10; The mass ratio of the first modified carbon-coated composite particles to urea is 100:8-10.

5. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S3: The mass ratio of lithium carbide to vinylidene fluoride is 1:1-2; The solid-liquid mass ratio of the lithium carbide and vinylidene fluoride to tetrahydrofuran is 1:9-10.

6. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S4: The molar ratio of the ammonium metavanadate to terephthalic acid is 1:1.5-2.

7. The method for preparing a long cycle high rate negative electrode material according to claim 1, characterized in that: In S4: The mass ratio of the metal-organic framework to lithium carbide is 1:0.3-0.5; The solid-liquid mass ratio of the metal-organic framework, lithium carbide and tetrahydrofuran is 1:8-9; The mass ratio of the pre-embedded lithium composite powder to polyacrylonitrile is 1:0.1-0.

2.

8. The method for preparing a long cycle and high rate negative electrode material according to claim 1, characterized in that: In S5: during pre-dispersion, the solid-to-liquid mass ratio of the surface-coated metal organic polymer and carboxymethyl cellulose to deionized water is 1:5-6.

9. A long cycle high rate negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The mass ratio of the metal organic polymer, carboxymethyl cellulose, modified composite particles, lithium fluorocarbon additive and conductive carbon black coated on the surface of the long cycle and high rate negative electrode material is: (4-5): (4-5): (75-80): (3-4): (3-5).

10. Use of a long-cycle high-rate negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in a lithium-ion battery.

Citation Information

Patent Citations

  • Non-metallic element doped silicon-oxygen negative electrode material and preparation method thereof

    CN112652769A

  • Long-circulation lithium battery negative electrode material as well as preparation method and application thereof

    CN116072831A

  • Preparation method of in-situ carbon-coated lithium ion battery material

    CN118448576A

  • Silicon-based composite negative electrode material for lithium ion secondary batteries, manufacturing method, and battery

    JP2015118911A

  • External shading device

    KR1020230035836A

Cited By

  • Regenerated silicon-carbon negative electrode active material, preparation method and application thereof, and lithium secondary battery

    CN122324816A